Design And Develop Robotic Arm For People With Disable Hands Using EMG And Gyroscope Sensor Control - Nawawi, Imam; Bastari, Winarno Fadjar; Widayaka, Parama Diptya (BEST, 2024)
Robotics technology is currently developing rapidly, including in the medical field. In this world there are many people with hand disabilities or patients who have amputations on their wrists, so they experience difficulties in carrying out their daily activities using their hands, such as to grasp objects. Then the thought arose to conduct research, with the aim of creating a Robotic Arm that could recognize 2 movements, namely the opening and clenching of the fingers like a hand in general. The Electromyogram sensor is used as a Robotic Arm control system, while the Gyroscope with Arduino as the control center. Based on the overall test results, the Robotic Arm can be moved with muscle contractions and user gestures to open and clench finger movements.